Effect of 1 wt% CoO addition on dielectric and microstructural behaviour of (SrO·TiO2)-(2SiO2·B2O 3) glass and glass ceramic - Thakur O.P.; Kumar D.; Parkash O.M.; Pandey L. (My University, 2025)
Glass of the nominal composition 64wt%(SrO·TiO2)-35 wt%(2SiO2·B2O3)-1 wt%(CoO) was prepared. The glass samples were subjected to heat treatment at 900 and 950°C. The phase progression in these glass ceramics from X-ray diffraction studies shows the formation of Sr2B2O5 as primary crystalline phase followed by rutile (TiO2), Sr3Ti2O7, SrB2Si2O8 and Sr3B2SiO8 as secondary phases. The first DTA exothermic peak of glass corresponds to the crystallization of Sr2B2O2, rutile and Sr3Ti2O5 phase while second crystallization peak may be assigned to the formation of SrB2Si2O8 and Sr3B2SiO8 phases. From microstructure studies we find that strontium borate grows with larger grain size whereas the other phases like Sr3Ti2O7,TiO2 appear smaller in size. Cobalt oxide content in the strontium titanate borosilicate glass ceramic gives the thermal stability to dielectric behaviour and decreases the dielectric loss.